2016
DOI: 10.1080/08897077.2015.1127870
|View full text |Cite
|
Sign up to set email alerts
|

Dental Opioid Prescribing Practices and Risk Mitigation Strategy Implementation: Identification of Potential Targets for Provider-Level Intervention

Abstract: Background Given the regular use of immediate release opioids for dental pain management, as well as documented opioid misuse among dental patients, the dental visit may provide a viable point of intervention to screen, identify, and educate patients regarding the risks associated with prescription opioid misuse and diversion. The aims of this statewide survey of dental practitioners were to assess: (a) awareness of the scope of prescription opioid misuse and diversion; (b) current opioid prescribing practices… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
49
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 37 publications
(53 reference statements)
4
49
0
Order By: Relevance
“…Some degree of dependence can develop even after a week of taking opioids regularly . A survey in the USA that assessed dentists’ knowledge and attitudes towards prescribing opioids found that there was a lack of training in the identification of prescription drug abuse and insufficient screening for opioid misuse and diversion . In addition, a study in Boston, Massachusetts, USA, found that approximately 12% of people presenting in the emergency department reporting backache, dental pain or headache were ‘drug seeking’ for an opioid medicine …”
Section: Discussionmentioning
confidence: 99%
“…Some degree of dependence can develop even after a week of taking opioids regularly . A survey in the USA that assessed dentists’ knowledge and attitudes towards prescribing opioids found that there was a lack of training in the identification of prescription drug abuse and insufficient screening for opioid misuse and diversion . In addition, a study in Boston, Massachusetts, USA, found that approximately 12% of people presenting in the emergency department reporting backache, dental pain or headache were ‘drug seeking’ for an opioid medicine …”
Section: Discussionmentioning
confidence: 99%
“…Therefore dentists should be aware of the increasing issues relating to prescribing drugs of dependence such as opioids and benzodiazepines and the importance of establishing a true therapeutic need . A cross sectional study of dentists in the US assessing dental opioid prescribing practices found a gap in existing dental training in the identification of prescription opioid diversion and screening for prescription drug abuse . Furthermore, a prospective, observational study of patients who presented at emergency departments in Boston showed that approximately 12% of patients reporting backache, dental pain or headache were ‘drug seeking’ for a medicine of dependence .…”
Section: Misuse Of Pharmaceutical Drugsmentioning
confidence: 99%
“…Medical prescribers’ contribution to the initiation and maintenance of the epidemic has been well documented . Dentists prescribe a notable volume of immediate release opioids, accounting for an estimated 12% of annual immediate release opioid prescriptions . Due in large part to the commonality of third molar extraction procedures, dental opioid prescribing is particularly frequent for adolescent patients, a group at increased risk for misuse …”
mentioning
confidence: 99%
“…[6][7][8][9] Dentists prescribe a notable volume of immediate release opioids, accounting for an estimated 12% of annual immediate release opioid prescriptions. [10][11][12][13][14] Due in large part to the commonality of third molar extraction procedures, dental opioid prescribing is particularly frequent for adolescent patients, a group at increased risk for misuse. [15][16][17][18] Rural communities have been particularly hard hit by the opioid epidemic and are disproportionately impacted by opioid-affected births and prescription opioid-related overdose.…”
mentioning
confidence: 99%